Analysis of Non-Performing Financing (NPF) After the Withdrawal of MSME Financing Relaxation: A Study at Bank Syariah Indonesia - Syaifuddin, Syaifuddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, the financing of Micro, Small, and Medium Enterprises (MSMEs) in Islamic banks should grow sustainably with controlled financing risks. However, the reality shows that after the revocation of the post-pandemic financing relaxation policy, there has been an increase in the potential for Non-Performing Financing (NPF), which puts pressure on the performance of Islamic banking, particularly Bank Syariah Indonesia. This study aims to analyze the dynamics of NPF in the MSME segment following the revocation of relaxation policies as well as the factors influencing financing smoothness. This article is categorized as qualitative library research using a descriptive-analytical methodology. The findings reveal that the revocation of relaxation policies has led to an increased risk of default, especially in small businesses that have not fully recovered from the pandemic’s impact. Nevertheless, continued restructuring strategies, strengthened risk management, and debtor assistance have proven effective in suppressing NPF growth and keeping it within reasonable limits.